First use of mini gamma cameras for intra-operative robotic SPECT reconstruction - Matthies, Philipp; Sharma, Kanishka; Okur, Asli; Gardiazabal, José; Vogel, Jakob; Lasser, Tobias; Navab, Nassir (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2013)
Different types of nuclear imaging systems have been used in the past, starting with pre-operative gantry-based SPECT systems and gamma cameras for 2D imaging of radioactive distributions. The main applications are concentrated on diagnostic imaging, since traditional SPECT systems and gamma cameras are bulky and heavy. With the development of compact gamma cameras with good resolution and high sensitivity, it is now possible to use them without a fixed imaging gantry. Mounting the camera onto a robot arm solves the weight issue, while also providing a highly repeatable and reliable acquisition platform. In this work we introduce a novel robotic setup performing scans with a mini gamma camera, along with the required calibration steps, and show the first SPECT reconstructions. The results are extremely promising, both in terms of image quality as well as reproducibility. In our experiments, the novel setup outperformed a commercial fhSPECT system, reaching accuracies comparable to state-of-the-art SPECT systems. © 2013 Springer-Verlag.
CRIS-Team Scopus Importer:2023-03-08